FEELINGS AROUSED IN THE FAMILIES OF PEOPLE HOSPITALIZED IN INTENSIVE CARE UNITS - Vanessa Maria Spohr; Hilda Maria Barbosa de Freitas; Silomar Ilha; Glaucia Dal Omo Nicola; Claudia Zamberlan; Maria Helena Gehlen (Universidade Federal do Paraná, 2013)
This is exploratory, descriptive research with a qualitative character, undertaken with eight family members of persons hospitalized in the Intensive Care Unit of a medium-size hospital located in the central region of Rio Grande do Sul, in the period August - September 2010, which aimed to investigate the feelings aroused in family members in relation to the environment and the health professionals. The data, collected through semi-structured interviews, was analyzed using the method of content analysis, from which emerged the categories Impotence in the face of the family member's hospitalization, Insecurity related to the closeness of death, Inflexibility of the health team regarding the family member, and Absence of dialog with the family members. The care for the family members is a need which must extend from professional development to the professionals' routine work. Thus, it becomes possible to assist the family members in coping with the illness and adapting to the hospitalization, demystifying the association of this environment with the event of death.